Computer-assisted interpreting tools: Tips and tricks from a professional interpreter - Goldsmith, Josh (My University, 2020)
The conference offers a general overview of the existing computer-assisted interpreting tools and the technology used in the preparation of the interpretation. It is also focused on terminology extraction, digital glossaries, the use of tablets during the interpretation (digital consecutive interpreting), hybrid interpreting modalities (SimConsec + SightConsec) and automatic speech recognition.
Keywords: Traducción; Enseñanza - Innovaciones; CAI tools; Interpreting; Interpreter; Tools; Terminology